Non-epileptic myoclonus and mitochondrial encephalomyopathy - A. Cukiert; F. G. M. Naylor; H. B. Scapolan; M. M. Vilela; F. S. Aloe; J. O. Siffert; Ana M. Tsanaglis; Monica Haddad; Teresa C. Machado; Mary Carvalho-Alegro; J. A. Levy; L. Marques-Assis (Arquivos de Neuro-Psiquiatria)
Two brothers presented to us with a progressive myoclonic syndrome with slight cerebellar symptoms. Neurological examination disclosed moderate cerebellar signs and pale optic discs; asymmetric, asynchronous and arhythmic myoclonus, an arthresthesic deficit and no muscular weakness. EEG background activity was moderately slow with no irritative discharges. CT was normal in both cases, Intermitent photic stimulation increased the frequency of the myoclonic jerks, which became bilateral and synchronous, progressing to a generalized tonic-clonic seizure. EPs and MRI in one case were normal. Anticonvulsant drugs were ineffective. The diagnosis of mitochondrial encephalomyopathy was based on the finding, in muscle specimens, of thickened basement membranes with myofibrillary degeneration and increased number of mitochondria peripherally distributed and with a dense granular matrix and some vacuoles. The clinical and EEG data suggest a. subcortical origin for this type of myoclonic syndrome.